PIKMA Role in Improving The Knowledge of Free Sex - Kartika Utami; Siti Rofi'ah; Nuril Nikmawati (Midwifery and Nursing Research, 2020)
Background : Youth is an asset and the future generation, so that young people had an important role to determine the future of Indonesia. Adolescents tend to want to know new things, so comes the behavioral want to try, and if it is driven by sexual stimulation can lead teens to get in on premarital sexual intercourse (sex). The purpose of this study was to determine the effectiveness of Pikma role in improving knowledge about sex with using the media module, singing Goldapersas, and leaflets to the students of SMK Negeri 2 Magelang Year 2019Methods : quasy experimental research type with pretest post test control group design. The population in this study as many as 282 people. a sample of 165 people. Data analysis by Kruskal Wallis and Mann Whitney Post Hoc test.Results : The results showed that there are different levels of knowledge between variables (singing Goldapersas, modules and leaflets) after being given health education, p = 0.000. The results of this study were expected to make teenagers more active in seeking information about reproductive health, in addition to the teachers also need to improve and equip students with knowledge about sex.Conclusion : Media module is more effective in supporting roles Pikma to increase knowledge about sex in adolescents.